'Friendship isn't an emotion fucknuts': Manipulating affective materiality to shape the experience of Homestuck's story. (December 2019) - Veale, Kevin
Homestuck is a textual and experiential chameleon that manipulates its own structure to shape the audience's affective experience of the story by mimicking not just the storytelling techniques of other media forms, but their modes of engagement as well. This article introduces terminology to illustrate how and why the online serial Homestuck qualifies as a distinctive form of storytelling. I introduce the term transmodal engagement to illustrate how Homestuck uses the affective, experiential affordances of different media forms to sculpt and shape the experience of the text in completely different ways to 'transmedia' storytelling. The second term this article introduces is metamedia storytelling, which describes how the audience's familiarity with storytelling across multiple media forms can be used to manipulate their experience of fiction. Homestuck deploys metamedia storytelling to continually destabilize the reader's understanding of the text and their investments in the storyworld by forcing re-evaluations of not just what is happening, but what kind of mediated relationship the readers have with the content of the story.